A decadal review of urban ornithology and a prospectus for the future. (2nd December 2016) - Marzluff, John M.
Abstract : The study of urban birds has increased exponentially in the last century. A prior review of the scientific literature up to the year 2000 found 100 research articles on urban birds, but in the past decade alone, over 1000 have been published. Here I review the studies from 2006–2015 to characterize their approach, location, general findings and recent obsessions, with an eye toward suggesting important future directions. Urban ornithology remains centred in the northern hemisphere, although there is a rapid increase in studies from southern, tropical and biodiverse settings. Studies in the north have changed from documentation of the composition of urban avifaunas to include many studies of the demographic response to aspects of urban environments. Studies of pattern remain most common in Latin America, Asia, Africa, New Zealand and the Middle East. Across the world, ornithologists are revealing the rapid evolution of behavioural and morphological adaptations by birds to the urban environment, much of which is due to phenotypic plasticity. The relationship of humans to nature generally and birds specifically has been increasingly studied as a driver of avifaunal change as well as a factor affecting human ethics. Urban ornithology remains rarely experimental, but it has matured to the point of supporting synthetic reviews and meta‐analyses that quantify the loss of avian diversity from city centres, characterize successful urban birds, discuss the role of amount and arrangement of vegetation on bird life, and explore the complex relationships between the subsidies and hazards of urban life and the survival and reproduction of birds. Yet much remains to be learned, including how some species thrive in cities with abundant predators; how city form and location affect the peak in avian richness that occurs typically at intermediate levels of urbanization; the significance of functional biotic homogenization; and the ways in which engaging citizens in urban bird life informs their broader environmental land ethic.